ANALISIS KOMPARATIF HUKUM CRYPTOCURRENCY DENGAN KONSEP MU’AMALAH KONSEP TABADUL MUQAYADLOH DAN HUQUQ AL-IKHTIRO’ WAL IBTIKAR - Ahmad; H. Mohammad Nasih Aschal (Fakultas Syariah dan Ekonomi Islam, Universitas Ibrahimy, 2021)
Cryptocurrency is a form of innovation and creativity from the history of the human journey in creating a system of exchange. Shari'ah provides free space (innovation and creativity) for humans to create the most effective and efficient system (وسائل). Cryptocurrency is a form of innovation and creativity in finding a system of exchange and storage media for goods (commodities).The research uses a comparative approach (comparison). The comparison made in this study is a comparison between Cryptocurrencies with the concept of currency (shorf) and nuqud as a transaction concept that is widely applicable. Furthermore, cryptocurrency is compared with the concept of mu'amalah barter transactions, as the most ancient transaction concept in human history. Cryptocurrencies are further compared with rights recognized in Copyright. The view that says that cryptocurrency is haram is based on the point of view of comparing cryptocurrency with currency (either nuqud or short).Cryptocurrencies are seen from the point of view of copyright (حقوق الإختراع الإبتكار) and the concept of barter transactions (مبادلة ), so it can produce different conclusions. From the point of view of this comparison of barter transactions with cryptocurrencies, it can be concluded that cryptocurrency is HALAL. Likewise, if the cryptocurrency law is examined with a Copyright approach, it results in the conclusion that cryptocurrency works are protected by religion and the law. Keywords: ,